Darwin Loves You : Natural Selection and the Re-enchantment of the World - Levine, George, 1931- (Book collections on Project MUSE., 2008)
Jesus and Darwin do battle on car bumpers across America. Medallions of fish symbolizing Jesus are answered by ones of amphibians stamped "Darwin," and stickers proclaiming "Jesus Loves You" are countered by "Darwin Loves You." The bumper sticker debate might be trivial and the pronouncement that "Darwin Loves You" may seem merely ironic, but George Levine insists that the message contains an unintended truth. In fact, he argues, we can read it straight. Darwin, Levine shows, saw a world from which his theory had banished transcendence as still lovable and enchanted, and we can see it like tha.